Cytokine regulation of glutamate decarboxylase biosynthesis in isolated rat islets of Langerhans. - Schmidli, R S (1996)
Insulin-dependent diabetes mellitus (IDDM) is an autoimmune disease in which cytokines are thought to play an important role in beta-cell destruction and immune regulation. A major target of beta-cell autoimmunity in IDDM is the enzyme glutamate decarboxylase (GAD). We hypothesized that cytokines in the insulitis lesion modulate the synthesis of GAD. This may, in turn, modify the rate of beta-cell destruction. Accordingly we cultured rat islets in the presence and absence of cytokines, and measured synthesis of both isoforms of GAD, GAD65 and GAD67, by [35S]methionine incorporation and immunoprecipitation with a rabbit antiserum that recognizes both GAD65 and GAD67. Incubation of islets with interleukin (IL)-1 beta (1 ng/ml, 24 h), tumour necrosis factor alpha (TNF-alpha; 200 units/ml, 24 h) or interferon gamma (IFN-gamma; 500 units/ml, 72 h) significantly decreased the synthesis of both GAD65 and GAD67, but reduced neither total protein synthesis nor insulin accumulation in the medium or content. Incubation of islets for 24 h in IFN-alpha (1000 units/ml), TNF-beta (50 ng/ml), IL 2 (1000 units/ml), IL-4 (100 ng/ml), IL-6 (10 ng/ml), IL-10 (20 ng/ml), IL-12 (10 ng/ml) or transforming growth factor beta 2 (TGF-beta 2; 5 ng/ml) did not significantly alter GAD65 or GAD67 synthesis. Inhibition of GAD65 and GAD67 protein synthesis by IL-1 beta, TNF-alpha or IFN-gamma was reversed by co-incubation with the nitric oxide synthase inhibitor, NG-monomethyl arginine (NMMA). Expression of both GAD65 and GAD67 mRNA, measured by RNase protection assay, was also decreased by IL-1 beta and completely restored to baseline levels by NMMA. Thus the synthesis of both isoforms of islet GAD is selectively decreased in the presence of IL-1 beta, TNF-alpha or IFN-gamma by a NO-mediated mechanism, probably at the level of cytokine gene transcription. As GAD autoimmunity has been previously shown to have a pathogenic role in an animal model of IDDM, its inhibition by cytokines might limit the immune response, thereby regulating the rate of beta-cell destruction in IDDM.